PERDAMAIAN ACEH PASCA BENCANA TSUNAMI ACEH 2004 DAN MOU HELSINKI: TELAAH KRITIS DISASTER DIPLOMACY PEMERINTAH INDONESIA DALAM PENYELESAIAN KONFLIK ACEH - Mudjiharto, Mudjiharto (JPP (Jurnal Politik Profetik), 2020)
This paper addresses and analyzes the fifteen years of peace in Aceh since the tsunami and MoU Helsinki. Analyzing Aceh peace after the disaster and MoU Helsinki was very important to understand how disaster diplomacy could make contribution to building pace in Aceh. This paper would discuss and analyze the Aceh peace building process, starting with the diplomacy process, before and after the tsunami hit Aceh. This paper aims to prove whether disaster could be used as diplomacy. In the case to know the process of disaster diplomacy to build peace in Aceh for 15 year, this paper used disaster diplomacy approach and the concept of peace building. This paper was based on a study using qualitative methods. The conclusion of this paper shows whether the Government of Indonesia was using disaster diplomacy to settle the Aceh dispute with GAM (Gerakan Aceh Merdeka). Disaster diplomacy from Indonesian government was proven to have a major contribution to the process of peace building in Aceh over a long period of time, not just at the time when the peace treaty was signed.